2016
DOI: 10.1177/0164027515602315
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Relationships and Parent Psychological Distress

Abstract: Relationships with children are important for parents’ psychological well-being, yet limited research addresses whether and how relationships with adult children matter for aging parents’ psychological well-being in mid- to later life. We used four waves of national longitudinal data (Americans’ Changing Lives, N = 1,692) and growth curve models to test how multiple dimensions of the intergenerational relationship—social support, strain, equity, and dissatisfaction—shape mid- to later life parents’ psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
(98 reference statements)
3
14
0
2
Order By: Relevance
“…The older study, conducted by Umberson (1992), found that parentally dissatisfied individuals had elevated levels of psychological distress (measured by an 11-item version of the Center for Epidemiological Studies Depression Scale), using cross-sectional data from a 1986 U.S. national survey of parents of offspring aged 16 years and older. The more recent study (Reczek & Zhang, 2016) reached the same conclusion, analyzing longitudinal data from the first four waves of the Americans’ Changing Lives panel study (1986-2001).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The older study, conducted by Umberson (1992), found that parentally dissatisfied individuals had elevated levels of psychological distress (measured by an 11-item version of the Center for Epidemiological Studies Depression Scale), using cross-sectional data from a 1986 U.S. national survey of parents of offspring aged 16 years and older. The more recent study (Reczek & Zhang, 2016) reached the same conclusion, analyzing longitudinal data from the first four waves of the Americans’ Changing Lives panel study (1986-2001).…”
mentioning
confidence: 71%
“…Parental dissatisfaction in later life has received little scholarly attention in the health and aging literature, not to mention the possible psychological mechanisms through which parental dissatisfaction may affect older parents’ health and well-being. Recent studies, however, point to the importance of exploring these areas of research (Reczek & Zhang, 2016; Thoits, 2011; Uchino, Bowen, Carlisle, & Birmingham, 2012). Drawing on relevant aspects of symbolic interactionism perspective, the life course perspective, and the stress process model, the current study examines the associations between parental dissatisfaction and four health and well-being outcomes and explores the underlying psychological pathways in a sample of older parents in China.…”
mentioning
confidence: 99%
“….. gerontology” (Brown, , p. 65). Although we focus on queering aging in the context of romantic relationships through a GAR framework, we direct readers to comprehensive overviews on queering aging by Reczek (), Brown (), and Fabbre ().…”
Section: Applying a Gar Framework In Research On Aging Romantic Relatmentioning
confidence: 99%
“…Parental satisfaction has been identified to be positively related to health and well-being in late life (Reczek and Zhang, 2015;Umberson, 1992). Much less is known, however, about the factors associated with parental satisfaction, which may operate differently at the various stages of the parental life course and across a variety of cultural contexts.…”
Section: Introductionmentioning
confidence: 99%